Ethylcelullose microspheres containing sodium diclofenac: Development and characterization - Baccarin, Marcelo A.; Evangelista, Raul C. [UNESP]; Lucinda-Silva, Ruth M. (My University, 2006)
The objective of the present study was the development and characterization of ethylcellulose microspheres containing diclofenac and the determination of the in vitro drug release profile. Microspheres were prepared by emulsification/solvent evaporation method using ethyl acetate as solvent for the polymer and water as non solvent. The microspheres were characterized by morphologic and granulometric analyses. The amount of encapsulated drug as well as its release profile in vitro were also determined. The product obtained was microparticles with smooth surface and narrow size distribution, about 50% of the particles being smaller than 5 μm. The methodology used allowed drug encapsulation with a good yield and the system provided a controlled release of diclofenac.
Keywords: Diclofenac; Ethylcellulose; Microencapsulation; diclofenac; ethyl cellulose; microsphere; drug delivery system; drug release; emulsion; in vitro study; methodology; microencapsulation; morphology